Hashtag Activism and Why #BlackLivesMatter In (and To) the Classroom - Cumberbatch, Prudence; Trujillo-Pagán, Nicole (Radical Teacher, 2016)
This paper considers #blacklivesmatter an important part of current discussions of race and social justice. It explores the ways in which Twitter users (and students) are developing a globally-connected voice to not only build awareness and solidarity, but also challenge the framing of issues relating to #blacklivesmatter and the ways blacks are represented by a variety of political actors, including the mainstream media. The paper identifies two trends in teaching #blacklivesmatter and its relevance to the classroom: historicizing the “new” civil rights movement and the use of testimony and discussion as a new praxis. The authors conclude that students must be reminded of their ability to influence their own lives by using their personal stories and seizing their voice.